Optimal contracting under adverse selection: The implications of mentalizing - Jonatan Lenells; Diego Stea; Nicolai J. Foss (Contemporary Economics, 2015)
We study a model of adverse selection, hard and soft information, and mentalizing ability-the human capacity to represent others' intentions, knowledge, and beliefs. By allowing for a continuous range of different information types, as well as for different means of acquiring information, we develop a model that captures how principals differentially obtain information on agents. We show that principals that combine conventional data collection techniques with mentalizing benefit from a synergistic effect that impacts both the amount of information that is accessed and the overall cost of that information. This strategy affects the properties of the optimal contract, which grows closer to the first best. This research provides insights into the implications of mentalizing for agency theory.
Keywords: D82; D83; 330; Adverse selection; mentalizing; hard information; soft information; contract